Clinical efficacy of ruxolitinib monotherapy and haploidentical hematopoeitic stem cell transplantation in a child with philadelphia chromosome-like relapsed/refractory acute lymphoblastic leukemia - Bayram, Nihan; Yaman, Yöntem; Özdilli, Kürşat; Telhan, Leyla; Nepesov, Serdar; Bilgen, Hülya; Elli, Murat; Behar, Sude Sema; Anak, Sema (Wiley, 2021)
Introduction (Ph-like) ALL is a subset of leukemia which has a gene expression profile similar to Ph+disease, but without the presence of BCR-ABL1 translocation. Case description We reported an exceptional case of a child with relapsed Ph-like ALL with IKZF1 gene deletion treated with high-dose ruxolitinib as monotherapy, after multi-agent chemotherapy. He remains in continued MRD-negative leukemia remission with full donor chimerism at 12 months post-HSCT. Discussion The circumstance that makes our case featured is the usage of ruxolitinib as monotherapy. This report, we believe, is a pioneering report for a frequent disease with a high risk of failure for the outcome.
Keywords: JAK Inhibitors; Philadelphia-Like ALL; Refractory ALL; Stem Cell Transplantation